2009
DOI: 10.1152/japplphysiol.91012.2008
|View full text |Cite|
|
Sign up to set email alerts
|

Arterial and pulmonary arterial hemodynamics and oxygen delivery/extraction in normal humans exposed to hyperbaric air and oxygen

Abstract: Weaver LK, Howe S, Snow GL, Deru K. Arterial and pulmonary arterial hemodynamics and oxygen delivery/extraction in normal humans exposed to hyperbaric air and oxygen. J Appl Physiol 107: 336-345, 2009. First published April 30, 2009 doi:10.1152/japplphysiol.91012.2008.-Divers and hyperbaric chamber attendants breathe hyperbaric air routinely. Hyperbaric oxygen (HBO2) is used therapeutically frequently. Although much is understood about the hemodynamic physiology and gas exchange effects during hyperbaric air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
3
26
1
Order By: Relevance
“…These findings are in contrast to previous reports that suggest resting cardiac output is reduced during hyperbaric hyperoxia (17,20,30,33). This discrepancy may be explained by the stroke volume being derived from the beat-to-beat brachial arterial pulse pressure wave using model flow analysis in the current study, whereas other studies have relied on thermal and indicator dilution methods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in contrast to previous reports that suggest resting cardiac output is reduced during hyperbaric hyperoxia (17,20,30,33). This discrepancy may be explained by the stroke volume being derived from the beat-to-beat brachial arterial pulse pressure wave using model flow analysis in the current study, whereas other studies have relied on thermal and indicator dilution methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, our estimated increase (ϳ25-30%) in arterial O 2 content during hyperoxia is based on calculated values of arterial PO 2 as described in METHODS. The estimated O 2 tensions from the current study are similar to those previously reported using direct measurements of Pa O 2 (i.e., micro-O 2 electrode or arterial blood sample) in subjects exposed to hyperbaric O 2 (8,19,29,30). Additionally, we were not able to calculate or determine whether O 2 consumption in the active forearm was different between trials.…”
Section: Discussionsupporting
confidence: 82%
“…HBA increases oxygen contents of the blood by about 2.5%, much less than the increase induced by HBO (30). A previous study using microarray analysis of neurons showed that HBA increases the expression levels of more genes than does normobaric oxygen (31).…”
Section: Discussionmentioning
confidence: 82%
“…Any increase in oxygen within the circulation comes from the increased alveolar partial pressure of oxygen during HBO exposure (Weaver et al 2009) and no changes in rates of oxygen delivery and consumption have been reported after HBO (Weaver et al 2009). Therefore, one could reasonably argue that HBO does not induce a significant stress response within the blood cell population.…”
Section: Discussionmentioning
confidence: 99%